The Cytotoxic and Anti-Migratory Properties of Caesalpinia sappan and Ficus septica, in Combination with Doxorubicin on 4T1 TNBC Cells with Nephroprotective Potential - Haryanti, Sari (Asian Pacific Organization for Cancer Prevention, 2022)
Objective: To evaluate the anti-cancer properties of Caesalpinia sappan and Ficus septica in combination with doxorubicin on 4T1 cells, confirm their nephroprotective activities, and predict the molecular targets of the underlying mechanisms. Methods: The cytotoxic activities of all extracts and doxorubicin were determined by MTT assay followed by cell cycle and apoptosis analysis using flow cytometry. Immunoblotting was used to determine the protein expressions. The proteins involved in the cell proliferation and migration were analyzed through bioinformatics approaches, whereas, the interaction between compounds and protein targets was observed through molecular docking. Furthermore, the effect of the extracts on cell migration was analyzed by scratch wound healing assay. The intracellular ROS after treatment with extracts was observed using DCFDA staining flow cytometry. Results: Both ECS and EFS performed cytotoxic properties and significantly enhanced doxorubicin’s cytotoxic effects against 4T1 cells. However, these cytotoxic activities did not correlate with the cell cycle progression. On the contrary, the combination treatment caused apoptosis that may correlate with the decreasing of IκBα phosphorylation, indicating that all agents targeted the inhibition of NF-κB activation. The combination treatments also inhibited cell migration and decreased MMP-9 expression. TNBC proliferation and metastasis needed at least 54 proteins to be activated, some of them are related to NF-κB activation. The inhibitory effect of ECS correlated with the interaction of brazilin and brazilein to IKK, a kinase protein that plays a role in IκBα phosphorylation. In addition, ECS and EFS reduced ROS expression in Vero cells caused by doxorubicin. Conclusion: In conclusion, ECS and EFS effectively enhanced the cytotoxic effect of doxorubicin and inhibit cell migration on 4T1 cells and these activities may correlate to the inhibitory effect of NF-κB activation. ECS and EFS also exhibit ROS suppressing effect on Vero cells that may be beneficent to reduce nephrotoxicity of chemotherapeutic treatment. © 2022, Asian Pacific Journal of Cancer Prevention. All rights reserved.